Hubungan Kualitas Tidur dan Aktivitas Fisik dengan Fungsi Kognitif pada Lansia di UPTD PSLU Tresna Werdh Natar Lampung Selatan - Ringgo Alfarisi; Ika Artini; Dessy Hermawan; Ajeng Febiyola (Universitas Malahayati, 2022)
ABSTRACT As you get older, there will be physical and psychosocial changes such as decreased cognitive function, there are several factors that can affect changes in cognitive function, some of the factors the sleep quality and physical activity. In some previous studies have also found that there is a relationship between sleep quality and physical activity with cognitive function in the elderly. This study was determined the relationship between sleep quality and physical activity with cognitive function in the elderly in UPTD PSLU Tresna Werdha Natar, South Lampung. This study is a quantitative study with a cross sectional approach. The population in the study were all elderlies at UPTD PSLU Tresna Werdha Natar South Lampung, in total 76 people. The population sample in total at this study was 76 people. Data collection used MMSE, Pittsburgh Sleep Quality Index (PSQI), IPAQ (International Physical Activity Questionnaire). Analysis of the relationship using the chi square test. The frequency distribution of respondents with light physical activity, as many as 44 respondents (68.8%), had good sleep quality, namely 36 respondents (56.3%), experienced cognitive dysfunction, as many as 35 respondents (54.7 %). There is a relationship between physical activity and cognitive function in the elderly (p value 0.016). There is a relationship between sleep quality and cognitive function in the elderly (p value 0.002). Conclusion: There is a relationship between the sleep quality and physical activity with cognitive function in the elderly in UPTD PSLU Tresna Werdha Natar, South Lampung. Keywords: Sleep Quality, Physical Activity, Cognitive Function ABSTRAK Semakin bertambahnya usia maka akan terjadinya perubahan fisik dan psikososial seperti penurunan fungsi kognitif, ada bebarapa faktor yang dapat mempengaruhi perubahan fungsi kognitif salah satunya adalah kualitas tidur dan aktivitas fisik. Beberapa penelitian sebelumnya juga mendapatkan bahwa adanya hubungan antara kualitas tidur dan aktivitas fisik dengan fungsi kognitif pada lansia. Penelitian ini untuk mengetahui hubungan kualitas tidur dan aktivitas fisik dengan fungsi kognitif pada lansia di UPTD PSLU Tresna Werdha Natar Lampung Selatan. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross sectional. Populasi pada penelitian adalah semua lansia di UPTD PSLU Tresna Werdha Natar Lampung Selatan sejumlah 76 orang, Sampel pada penelitian ini adalah total populasi sejumlah 76 orang. Pengumpulan data menggunakan MMSE, Pittsburgh Sleep Quality Index (PSQI), IPAQ (International Physical Activity Questionnaire). Analisis hubungan menggunakan uji chi square. Distribusi frekuensi responden dengan aktivitas fisik ringan, yaitu sebanyak 44 responden (68,8%), kualitas tidur baik, yaitu sebanyak 36 responden (56,3%), mengalami gangguan fungsi kognitif, yaitu sebanyak 35 responden (54,7%). Ada hubungan aktivitas fisik dengan fungsi kognitif pada lansia (p value 0,016). Ada hubungan kualitas tidur dengan fungsi kognitif pada lansia (p value 0,002). Terdapat hubungan antara kualitas tidur dan aktivitas fisik dengan fungsi kognitif pada lansia di UPTD PSLU Tresna Werdha Natar Lampung Selatan. Kata Kunci: Kualitas Tidur, Aktivitas Fisik, Fungsi Kognitif